Perancangan Palopo Civic Learning Center di Kota Palopo - Apriyanto Yauwri (Intra, 2017)
Library in Palopo, South of Sulawesi in general builded by government that looking for information and gives knowledge and kind of services that must have general character. In other word it provides some of information and give services to all People in Palopo. So, Library Interior Design has important thing in library design development. But, just a few library that willing to collect the fund for interior design development, much of them move to additional collection. When a good interior design , cause the library visitor feels comfortable, safe and productive.